Predictors of the development of placental dysfunction and methods for its correction in patients with retrochoric hematoma in the I trimester of gestation - О. В. Кравченко; І. В. Бойко (Publishing House TRILIST, 2018)
The objective of study was to determine the predictors of the development of placental dysfunction and to develop methods for its prevention and treatment in patients with retrochoric hematoma in the first trimester of gestation. Patients and methods. Under observation, there were 58 pregnant women with retrochoric hematoma in the first trimester (main group) and 20 women with a physiological pregnancy (control group). All pregnant women underwent a standard clinical and laboratory examination. In the ultrasound study, the volume of the retrochoric hematoma, its localization, and also the coccygeal-parietal size of the embryo, the heart rate, the volume of the fetal egg, the mid-inner diameter of the yolk sac, the vascularization of the yellow body, the hemodynamics in the myometrium were assessed. In a transvaginal ultrasound study, a special three-dimensional VOCAL program was used to calculate the chorion volume and evaluate its vascular system. Results. Predictors of placental dysfunction in the detachment of the chorion in the I trimester of gestation are associated not only with the volume and localization of the retrochoric hematoma, but also, first of all, with the state of extraembryonic structures. Decreased vascularization of the chorion, its hypoplasia, pathological nature of the blood flow in the yellow body, and hemodynamic disturbances in the myometrium creates high risks of placental dysfunction and worsens the pregnancy prognosis. The developed preventive measures include the 3 stage of treatment, the medicament means are aimed not only at halting the bleeding, but also on the effective restoration of microcirculation and the provision of adequate conditions for the passage of the second wave of trophoblast invasion. Conclusion. The proposed three-step corrective therapy contributes to the normalization of uterine-chorionic blood flow, the restoration of effective embryochorial interrelations and significantly reduces the incidence of placental dysfunction in the future.